Minimum wage policy and inequality in Latin America and the Caribbean - Thomas Gindling; Lucas Ronconi (Inter-American Development Bank (IDB), 2023)
In this chapter reviews the literature and inform policy debates about the effects of minimum wages (MW) on income inequality in Latin America and the Caribbean (LAC).
Keywords: D31; J38; J46; K42; 330; Labor Force; Politics; Wage; Income; Inequality; Labor; Equality; Minimum Wage; Income Equality; Household Income